Habilidades visuoconstrutivas não grafomotoras no envelhecimento saudável e patológico - Rodrigues, Rafaela Martins (2019)
Neuropsychological assessment of visuoconstructive abitilies of the elderly is generally limited to two-dimensional measures of graphomotor tasks, while other modalities remain neglected, even with evidence that they are sensitive to detect visuoconstructive deficits. To date, we have not found studies that jointly evaluate two-dimensional, three-dimensional and mental non-graphomotor measures in elderly patients suffering from Alzheimer's Disease (AD) or Mild Cognitive Impairment (CCL). The aim of this study was to investigate the relationship between the different components of visuoconstructive abilities in the pathological aging process compared to healthy aging and to analyze the sensitivity and specificity of these components to detect AD and CCL. Were included 41 participants, 16 of whom had CCL, 10 had AD, and 15 were cognitively healthy elderly (CG). All volunteers underwent an extensive neuropsychological evaluation, which included non-graphomotor two-dimensional, three-dimensional and mental visuoconstructive task, in verbal command and copy modalities. The results indicated that, with the exception of the Stick Test, all measures found differences between groups, in which the lowest scores occurred in the AD group, followed by CCL and CG. The most consistent measures of discrimination between groups were found in the three-dimensional and mental tasks both by verbal command. These results indicate that other variations of visuoconstructive measures besides grafomotors are already compromised in the initial phase of AD and CCL and have relative sensitivity to the degenerative process. The findings also show evidence of the dissociation between visuoconstructive tasks, so that they cannot be considered equivalent during the evaluation of visuoconstructive deficits.